AN INTEGRATED MODEL OF INFLUENCE OF PERCEIVED QUALITY, PERCEIVED VALUE, BRAND ASSOCIATION, BRAND AWARENESS AND BRAND UNIQUENESS ON BRAND LOYALTY TOWARDS A LUXURY BRAND IN BANGKOK, THAILAND - Chansuk, Suwanan; Chaipoopirutana, Sirion (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Under today's increasingly competitive business environment, maintaining customers' brand loyalty remains a significant factor. To be successful in any business sector, companies should understand the customers' needs and create strong brands to attract a long-term business. The primary purpose of this study is to investigate the factors affecting brand loyalty towards the top luxury brand in Bangkok, Thailand. The researchers collected data from 400 consumers in front of the main gate of four shopping malls, including both Thai males and females in Bangkok. The individuals whom we conducted all had experienced purchasing luxury products by using five-point Likert scale survey questionnaires. The non-probability was applied to collect the data from the sampling units by using judgment, quota, and convenience sampling techniques. The descriptive, interferential, and linear regression analysis was used to test all hypotheses. Based on the result of this study, the researchers found that brand awareness has a significant influence on perceived quality and brand association. Additionally, brand loyalty is significantly influenced by perceived value, brand uniqueness, perceived quality, brand awareness, and brand association, respectively.